Social Construct of Masculinity Towards Mental Health: A Literature Review (European Journal of Behavioral Sciences, 2023)
Masculinity is trait that exist in both male and female. However, masculinity values develop into social constructs affecting various aspects of life, one of which is mental health. It is important to understand how individuals internalize the construct that contributes to their psychological dynamics. This study aims to determine the impact of masculinity construct and the role of mental health literacy on mental health through a literature review. The results show that some aspects in the construct of masculinity, such as self-reliance, dominance, and emotional restraint, inhibit people’s mental health behavior, such as decreasing help-seeking behavior and self-disclosure, and increasing maladaptive coping. However, another study reports that the masculinity construct also affects women as well as men and the related studies remain very limited. It is imperative to improve mental health awareness that is sensitive to the influence of gender roles and its impacts on mental health.